Manusia Dalam Perspektif Al Qur’an Studi Komparasi Pemikiran As-Syaukany dan Sayyid Qutb - Aminatuz Zahro (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
Man is a creature of God who has a component of heart, mind and body. From his heart was born 'azm (determination), from his mind was born knowledge and from his body was born action. [1]These three components are great potential that must be maintained and used properly and correctly. On the one hand, man is facilitated by being blown away by his spirit, given many privileges beyond any other makhluq. But on the other hand, he was burdened with worship, the necessity of doing truth and goodness, unlike other makhluq. Although he was given the freedom to choose for faith or kufr, he must be held accountable for all his deeds and be rewarded with heaven or hell. Therefore, humans have different roles and responsibilities than other creatures. This study uses a comparative method that compares and analyzes the thoughts of asy-Shaukany in the book of fathul qodir and the thoughst of Sayyid Qutb in the book of fi dzilal Al- Qur'an about humans in the perspective of the Qur'an. As for the discussion, researcher uses the approach of science interconnection and the technique of literature studies (library research), while the data analysis method used is content analysis. The uniqueness of man in the view of the Qur'an through the thought of the mufassir can be seen from several aspects. Among them are the terminology in the Qur'an, the process of its occurrence, the secret of its diversity, its role and responsibilities.